Accuracy of Demirjian's and Indian-specific formulae in age estimation using eight-teeth method in Kanyakumari population - S Akhil; T Isaac Joseph; K L Girish; Pradeesh Sathyan (Wolters Kluwer Medknow Publications, 2019)
Background: Most of the scientific formulae for age estimation in forensic odontology were tested among western population and hence cannot be applied to the Indian population consistently. Therefore, it was in this context that Dr. Ashith B. Acharya had carried out a study using the modified Demirjian's method in Indian population and found out that the study gave inferior results for age estimation. So he developed Indian-specific regression analysis and worked out a formula. Aim: This study was done to validate age using Demirjian's eight-teeth method and to compare the effectiveness of Demirjian's formula and Indian-specific formula in Kanyakumari population. Material and Methods: Digital orthopantomographs of 150 patients fulfilling the inclusion and exclusion criteria in the age group of 8-24 years were used in the study. The third quadrant in the radiograph was assessed visually from mandibular central incisor to the third molar using Demirjian's modified criteria chart. Calculation of the dental age was done using Demirjian's formula and Ashith B. Acharya's Indian-specific formula. The difference between chronological age and dental age was calculated, and the mean absolute error (MAE) was obtained. Results: The MAE was 0.20 years for the whole of Kanyakumari population, and for males it was 0.10 years and for females 0.29 years with Indian-specific formula, whereas the MAE was 2.66, 1.86, and 3.51 years, respectively, for the whole of Kanyakumari population, males, and females using Demirjian's formula. Conclusion: The observations from this study suggest that the MAE was less between chronological age and estimated dental age which was calculated using Indian-specific formula, compared with the values obtained using Demirjian's formula. Thereby we conclude that Indian-specific formula is more reliable in age estimation of Kanyakumari population.